An Empirical Evaluation Of The Potential Of Public E-Procurement To Reduce Corruption - Neupane, Arjun; Soar, Jeffrey; Vaidya, Kishor (Australasian Journal of Information Systems, 2014)
One of the significant potential benefits of e-procurement technology is reducing opportunities for corruption in public procurement processes. The authors identified anti-corruption capabilities of e-procurement through an extensive literature review and a theoretical model representing the impact of three latent variables: monopoly of power, information asymmetry, and transparency and accountability upon the dependent variable, the intent-to-adopt e-procurement. This research was guided by the Principal-Agent theory and collected the perceptions of 46 government officers of the potential of public e-procurement to reduce corruption in public procurement processes. Results were analysed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The findings suggest that the intent-to-adopt e-procurement has a positive and significant relationship with the independent variables that might inform developing countries in strategies to combat corruption in public procurement.